Strategic Alliances and Organizational Performance of Selected Manufacturing Firms in Ogun State, Nigeria - Okafor, Linus I.; Bello, Bashiru A.; Onifade, Temitayo A.; Ogunbiyi, Margaret E.; Opele, Adedayo M.; Elufisan, Olaronke O.; Hamzat, Bolaji S.; Olusanmi, Alabi E.; Nnoli, Ikenna T.; Abiodun, Oloyede (International Review of Management and Marketing, 2026)
The study examined the impact of Strategic Alliances on the Performance of Manufacturing Firms in Ogun State, Nigeria. Data from a questionnaire survey conducted among three hundred and seventy-five (375) employees of seven manufacturing firms were analysed using statistical methods. The Pearson correlation coefficient revealed a significant relationship between technological strategic alliance and firm performance (0.745 and p<0.01), as well as between marketing strategic alliance and firm performance (0.878 and p<0.01). Multiple regression analysis further confirmed that both technology (β = 0.239) and marketing (β = 0.752) strategic alliances had a positive and significant impact on firm performance. Based on these findings, the study recommends that policymakers should promote and support manufacturing firms in forming strategic alliances, particularly in technology and marketing sectors, to enhance their performance.